The role of concomitant chemoradiotherapy in AJCC 7th edition T1-2N1 oropharyngeal carcinoma in the human papillomavirus era. (November 2020) - Lu, Diana J.; Luu, Michael; Nguyen, Anthony T.; Shiao, Stephen L.; Scher, Kevin; Mita, Alain; Anderson, Eric; Clair, Jon Mallen-St.; Ho, Allen S.; Zumsteg, Zachary S.
Highlights: Radiotherapy alone is a standard of care for AJCC 7E T1-2N1 oropharyngeal cancer according to NCCN guidelines. Virtually no comparative data of radiotherapy vs chemoradiation exists in this population. Chemoradiation (CRT) was associated with improved survival in this cohort. Magnitude of benefit from CRT was at least as strong in HPV(+) as in HPV(−) patients. Abstract: Background: Radiotherapy (RT) without chemotherapy is considered a standard of care for the management of American Joint Committee on Cancer (AJCC) 7th edition (7E) T1-2N1 oropharyngeal squamous cell carcinoma (OPSCC). Recent data suggests concurrent chemoradiation (CCRT) may benefit these patients but did not include human papillomavirus (HPV) status. Given the radiosensitivity differences between HPV-positive versus HPV-negative OPSCC, the effect of chemotherapy may differ in these patients. Methods: We analyzed patients in the National Cancer Database diagnosed between 2010 and 2015 with AJCC 7E stage cT1-2N1M0 OPSCC and known HPV status undergoing definitive RT or CCRT. Results: Overall, 1964 patients were included, including 1297 (66%) HPV-positive and 667 (34%) HPV-negative patients. 66% received CCRT and 34% received RT alone. In multivariate analysis, CCRT was associated with improved survival compared with RT alone (hazard ratio [HR], 0.70; 95% confidence interval [CI], 0.57–0.87; P = 0.001). In propensity score-matched cohorts, 4-year overall survival was 87.4% vs 78.4% in HPV-positive patients receiving CCRT and RT alone, respectively (P = 0.002), and 65.5% vs 58.9% in HPV-negative patients, respectively (P = 0.2). There was no evidence that HPV-positivity diminished the association between CCRT and longer survival (HR, 0.57; 95% CI, 0.42–0.81) versus what was observed in HPV-negative patients (HR, 0.86; 95% CI, 0.64–1.16) (interaction P = 0.06). Conclusions: CCRT is associated with improved survival in AJCC 7E T1-2N1 OPSCC. Despite the radiosensitivity of HPV-positive OPSCC, the association of CCRT with improved survival for T1-2N1 HPV-positive OPSCC was at least as strong, if not stronger, than what was observed in HPV-negative patients.